Richard Dawkins : how a scientist changed the way we think : reflections by scientists, writers, and philosophers - Grafen, Alan; Ridley, Mark (Oxford University Press, 2006)
This sparkling collection explores the impact of Richard Dawkins as scientist, rationalist, and one of the most important thinkers alive today. Leading figures from science, philosophy, literature, and the media reflect on the breadth and range of Dawkins' contributions to science and public debate, from evolutionary theory and artificial life, to rationalism and ethics. - ;This sparkling collection explores the impact of Richard Dawkins as scientist, rationalist, and one of the most important thinkers alive today. Specially commissioned pieces by leading figures in science, philosophy, litera.
Keywords: Dawkins, Richard, -- 1941- -- Influence.; Dawkins, Richard, -- 1941-; Behavior genetics.; Evolution (Biology); Genetics, Behavioral; Evolution; Biological Evolution; Biology -- General.; Biology.; Health & Biological Sciences.; Génétique du comportement.; Évolution (Biologie); evolution.; SCIENCE -- Life Sciences -- Zoology -- General.; Behavior genetics; Influence (Literary, artistic, etc.); Electronic books.; Essay; essays.; Essays; Essays.; Essais.